Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00500-016-2283-y
|View full text |Cite
|
Sign up to set email alerts
|

MOCDroid: multi-objective evolutionary classifier for Android malware detection

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Martín et al [34] illustrated outsider calls to sidestep the impacts of these disguise methodologies since they can't be obfuscated. We join bunching and multi-target advancement to produce a classifier in view of particular practices characterized by outsider call bunches.…”
Section: Review Of the Signature-based Approachesmentioning
confidence: 99%
“…Martín et al [34] illustrated outsider calls to sidestep the impacts of these disguise methodologies since they can't be obfuscated. We join bunching and multi-target advancement to produce a classifier in view of particular practices characterized by outsider call bunches.…”
Section: Review Of the Signature-based Approachesmentioning
confidence: 99%
“…However, such outsider calls provide essential information for software analysis and should be obfuscated. For example, Martín et al (2017) showed that the function calls of third-party libraries are very effective for signature-based malware detection (Souri and Hosseini 2018). To obfuscate such information, Collberg et al (1997) suggested substituting common patterns of function invocation with less obvious ones.…”
Section: Code Diversificationmentioning
confidence: 99%
“…In [74], a static analysis framework called MOC-Droid has been proposed to discriminate malware and benign-ware. A semantic intention has been extracted from third-party API call combinations (Import terms) and two sub-models that keep only relevant behaviours for malware and benign applications have been created.…”
Section: Code-based Featuresmentioning
confidence: 99%
“…Each of DexClassLoader and Crypto APIs have been used in [77]. Also, other features such as Import terms were used in [74]. Moreover, the method calls and function arguments and instructions were used in [78].…”
Section: Code-based Featuresmentioning
confidence: 99%